How I treat HER2-low advanced breast cancer - Ilana Schlam; Sara M. Tolaney; Paolo Tarantino (Breast, 2023)
Introduction: Targeting low levels of human receptor epidermal growth factor 2 (HER2) expression has reshaped the treatment paradigm for half of the patients with advanced breast cancer. HER2-low is currently defined as a HER2 immunohistochemical expression of 1+ or 2+ without amplification by in-situ hybridization. Until recently, HER2-targeted agents were ineffective in treating patients with HER2-low disease. Areas covered: In this narrative review, we summarize the current management of HER2-low breast cancer. We highlight the findings of the DESTINY-Breast 04 phase 3 trial, which confirmed the efficacy of trastuzumab-deruxtecan (T-DXd) for the treatment of patients with advanced, pretreated HER2-low breast cancer. We also discuss how to implement this new treatment option in treatment algorithms of hormone receptor (HR)-positive and triple-negative tumors, as well as how to optimally manage selected toxicities of T-DXd. Expert opinion: T-DXd is currently the standard of care for patients with advanced, pretreated, HER2-low breast cancer. Based on the design of the DESTINY-Breast04 trial, the current optimal place in treatment algorithms is after the first line of chemotherapy, both in HR-positive and triple-negative breast cancer. Up to 10–15% of the patients receiving T-DXd are expected to develop interstitial lung disease, which in 1–2% of the cases can be fatal. Adequate monitoring and prompt management are required to minimize the impact of ILD and to safely implement T-DXd in clinical practice.